Ð˜Ð·ÑƒÑ‡ÐµÐ½Ð¸Ðµ Ð²Ð»Ð¸ÑÐ½Ð¸Ñ Ñ…Ð¾Ð»Ð¾Ð´Ð¾Ð²Ð¾Ð³Ð¾ Ð·Ð°ÐºÐ°Ð»Ð¸Ð²Ð°Ð½Ð¸Ñ ÐºÐ°Ñ€Ñ‚Ð¾Ñ„ÐµÐ»Ñ Ð½Ð° ÑÐ¾Ñ…Ñ€Ð°Ð½Ð½Ð¾ÑÑ‚ÑŒ Ð¼ÐµÑ€Ð¸ÑÑ‚ÐµÐ¼, ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… Ð¼ÐµÐ´Ð»ÐµÐ½Ð½Ñ‹Ð¼ Ð·Ð°Ð¼Ð¾Ñ€Ð°Ð¶Ð¸Ð²Ð°Ð½Ð¸ÐµÐ¼ - Stribul, T. F.; Shevchenko, N. A.; Rozanov, L. F. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
Cold hardening effect on potato meristem integrity at two-step cryopreservation has been studied. Such cryoprotectants as dimethyl sulfoxide (DMSO) and 1,2-propanediol (1,2-PD) have been used. Freezing of hardened potato apexes under DMSO protection was established to increase their integrity in comparison with the same index in non-hardened meristems. Potato apex hardening is inexpedient when using 1,2-PD. Observation for cryopreserved meristem development within 30 days has demonstrated that treatment with cryoprotectants and freezing inhibit an apex growth in comparison with the control. 1,2-PD occurred to be less toxic. DMSO treatment can cause callus-genesis.